Upgrading Bio-Oil Produced from Corn Cobs and Cedrela odorata via Catalytic Olefination and Esterification with 3,7-Dimethyloct-1-ene and Butanol - Folasegun A. Dawodu; Olubunmi O. Ayodele; John O. Akintola; Oluwamayokun A. Obembe; Ameerah O. Sanni; Bosede D. Agbejinmi (International Journal of Chemical Engineering)
In this study, corn cobs (CC) and Cedrela odorata (CO) sawdust which are common waste materials in Nigeria were used as raw materials in the production of bio-oil through pyrolysis at 500°C, for 2 h. The biochar produced in the process was sulfonated with concentrated sulfuric acid under reflux at 150°C for 6 h and used as a solid acid catalyst for bio-oil upgrading. The bio-oil was upgraded by simultaneous olefination and esterification using 3,7-dimethyloct-1-ene and butanol which served as a reagent and cosolvent. FT-IR spectra of the activated biochar from CC and CO raw materials showed an absorbance in the range of 1032–1180 cm−1, which is indicative of asymmetric S=O bonds, and the spectra also revealed a band between 3400 and 3700 cm−1, which indicated presence of hydrogen-bonded hydroxyl groups and thus successful activation of the biochar. This observed IR absorbance was absent in the nonactivated biochar. Proximate analysis of upgraded bio-oils revealed a significant reduction in percentage water and oxygen contents, an increase in the high heating value (HHV) and flammability. The chemical composition of the bio-oils was determined using GC-MS, and it showed significant reduction in oxygenated compounds in the upgraded bio-oil as against their high composition in raw bio-oils.